Economic Development in Africa 2008 - Conference des Nations Unies sur le commerce et le développement (United Nations, 2008)
This year’s report examines Africa’s export performance after trade liberalization in order to draw lessons for use in the design of future development strategies. It identifies Africa’s weak supply response as the most important impediment to the continent’s export performance, suggesting that future export policies should focus more on ways to increase production for export. The publication proposes some policies that could help Africa to refocus its development priorities on structural transformation in order to increase the continent’s supply capacity and export response.